Mineralization of fipronil using solar light-induced ZnO/Co3O4 photocatalyst@ceramic substrate: Optimization of parameters by RSM. (June 2023) - Zeshan, Muhammad; Bhatti, Ijaz Ahmad; Mohsin, Muhammad
Highlights: ZnO@CP, Co3 O4 @CP and ZnO/Co3 O4 @CP were fabricated by Spray Pyrolysis and characterized by XRD, SEM, EDX, UV-Vis and FTIR. Photocatalytic activity of fabricated materials were evaluated by applying on photodegradation of FP pesticide. Optimization of reaction parameters were done by RSM and of FP pesticide mineralization was done by UV/Vis and FTIR analysis. Water quality parameters such as BOD, COD and TOC were also examined before and after treatment. The most important factor reusability of fabricated material was also investigated at optimum condition. Abstract: Mineralization of organic compounds especially fipronil (FP) pesticide is a major concern, while its metabolites exhibit significant toxicity, which poses a significant threat to human health and the environment. Here, ZnO, Co3 O4, nanoparticles and ZnO/Co3 O4 nanocomposite thin films have been fabricated on ceramic plate by spray pyrolysis method. The central composite design (CCD) method under response surface methodology (RSM) is used to optimize operational parameters and 94.95% mineralization was achieved at optimum conditions. The photocatalytic mineralization of FP pesticide has been evaluated by FTIR and UV/Vis spectroscopic techniques, and the disappearance of the main characteristics peaks indicate the mineralization of the FP pesticide. Moreover, the fabrication of catalyst over CP imparted promising reusability and stability that maintained ∼ 100% performance for the first 3 cycles of FP pesticide treatment. However, after the 3rd cycle, it began to decline and dropped to 64.03% when the 26th cycle was administered. Graphical abstract: Image, graphical abstract